National Institutes of Health Career Development (K) Awards to Young Surgeons: An Academic Milestone or One-hit Wonder?. Issue 4 (October 2021) - Mesquita-Neto, Jose Wilson; Dailey, William; Weaver, Donald; Datta, Jashodeep; Macedo, Francis I.; Merchant, Nipun B.
Abstract : Objective: To assess contemporary trends in the National Institutes of Health (NIH) Career Development (K) Awards within the Departments of Surgery and its impact on the likelihood of achieving independent R01 grants. Background: The NIH provides K-type Career Development Awards to nurture young clinicians toward a productive academic career, thereby maintaining a pipeline of physician-scientists. However, the impact of K awards on career trajectory of surgeons remains unclear. Methods: The NIH grant data was queried for all new K08/K23 grants awarded to Departments of Surgery (1999–2019). Principal Investigators' data and grant-related information was obtained. Results: The NIH awarded 298 K08/23 surgical grants (41, 893, 170) over the last 2 decades. Median budget increased from 116, 370 to 167, 508 ( P <0.001). Of grantees, 83.2% were MDs, 15.1% MD/PhD, and 1.7% PhDs, with 25.2% being women. Principal Investigators' were mostly practicing surgeons (91.1%) with fellowship training (82.4%) and young in their careers 4 [interquartile ranges (IQR) 4] years of experience. Vascular surgery (15.9%), Complex General Surgical Oncology (15.1%), and Trauma/Critical Care (14.6%) were the most frequent specialties. Awards were associated with 3, 336 publications [median 8/project (IQR 13)]. The majority of K grantees (77.2%) currently hold an academic faculty position. Only 32.2% of awardees received independent R01 grant funding, at a median of 5.5 years (IQR 5) after their K awards. Sex ( P = 0.71), previous fellowship training ( P = 0.63), type of surgical specialty ( P = 0.72), or MD/PhD degree ( P = 0.75) were not associated with increased likelihood of achieving a subsequent R01 award. Conclusion: Although the majority of K awardees maintain an academic career, only a limited number of grantees progress to obtain NIH R01 funding. Increased mentorship, financial support, and infrastructure are needed to facilitate career development awardees opportunities to enhance their ability to achieve independent funding.